The Role Of Business Administration In The Implementation Of Organizational Communication Within The Warung Tegal Franchise Network In The Jabodetabek Area - Noviana Tursanurohmad; Made Wilantara; Misnan Misnan; Iswahyu Pranawukir (ETTISAL : Journal of Communication, 2024)
This study aims to analyze the role of business administration in implementing organizational communication within the Warung Tegal (Warteg) franchise network in the Jabodetabek area. The research employs a qualitative descriptive method, focusing on analyzing the realities faced by the Warteg franchise network regarding business administration and organizational communication. The findings reveal that although the Jabodetabek Warteg franchise has adopted the franchise model, its impact on elevating the status of traditional Warteg establishments remains insignificant. Several positive factors were identified, including (1) profitability due to the provision of staple foods, (2) an automated operational system that does not require startup or specific marketing strategies, (3) a well-established brand, (4) a clear operational system, (5) a modern 3S (Neat, Clean, Compact) building concept, and (6) an effective application of the GFC (Good, Fast, Cheap)principle. However, there are still some limitations, such as (1) a lack of strong positioning, both functionally (addressing hunger) and emotionally (appealing to a specific consumer segment), (2) the productâ€™s brand character has not achieved top-of-mind awareness among consumers, (3) a lack of differentiation in terms of taste or customer experience, (4) suboptimal location strategy due to limited parking space, and (5) challenges in meeting online order demands. Additionally, the study uncovers opportunities for further development, such as flexible partnership packages that offer a quick return on investment, well-established managerial SOPs, franchisers assisting with location selection, and a cooperative leadership role. A key finding is that, among seven Warteg franchises, the â€œNew Bahariâ€ (WNB) network has successfully implemented digital technology through an ERP (Enterprise Resource Planning) system with real-time control applications, YouTap POS and YouTap BOS.